Visual Assessment of The Quality Of Landscape Design in Paya Indah Wetlands, Malaysia - Hussein, Mohd Kher (2005)
Visual quality of landscape is becoming an important element in em-friendly design for nature-based tourism areas in Malaysia. However, the majority of the man-made landscape elements of nature-based tourism areas such as buildings do not harmonize with the natural environment and are considered as not em-friendly in design. A study was conducted in Paya Indah Wetlands aimed at assessing visual rating and perception of the man-made landscape using expert judgment technique. This study used selected photographs of the man-made landscape elements in Paya Indah Wetlands representing different types of buildings, park furniture, parking features, pedestrian facilities, drainage and signage. The scoring scheme for visual quality and landscape features was valued using the six basic design elements, namely, form, line, colour, texture, shape and space. Data were gathered from 100 experts using a structured questionnaire with surrogated photos, distributed equally among landscape architects and architects. The results revealed that the visual quality of Paya Indah Wetlands were categorized as moderate in quality, and some of the elements were considered as of poor quality. The results of regression analysis revealed that the visual rating was affected significantly by the respondents' age, sector of employment and professional memberships in certified bodies. The Mann-Whitney and Kruskal-Wallis test revealed that the differences in visual rating differed with regards to the education background, sector of employment and professional membership. From the results, the basic design elements (form, line, colour, texture, shape and space) shouId be taken into consideration at the early stage in the design process to lend a higher visual quality to the wetland landscape of Paya Indah Wetlands.